2022
DOI: 10.18778/1733-8077.18.1.04
|View full text |Cite
|
Sign up to set email alerts
|

“If Things Really Go On as They Are at the Moment, Then I Will Work Illegally. End of Story.” Pandemic Realities in Marginalized Entrepreneurships

Abstract: Micro-enterprises and self-employed individuals have been hit particularly hard by the economic effects of the COVID-19 pandemic, but few studies have tackled the issue. This paper is based on four in-depth case studies of self-employed people from different sectors who have been greatly affected by measures taken to control the pandemic. By capturing shifts in the perception of institutional and economic pressures, as well as precarity after the outbreak of COVID-19, we gained profound insight into crisis man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Part of the reason for increased risk of violence correlated with the pressure for sex workers to meet clients at their homes (Hassan et al, 2023-Kenya); sex workers in Mozambique reported hearing stories of violent crimes and murders occurring in client homes (Aantjes et al, 2023). Due to the criminalization of sex work, sex workers in Germany were reluctant to come forward if assaulted (Tümpel & Cardone, 2022). Participants in a study from the Dominican Republic also reported an increase in verbal, emotional and physical abuse from partners (Wang et al, 2022).…”
Section: Aggression and Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Part of the reason for increased risk of violence correlated with the pressure for sex workers to meet clients at their homes (Hassan et al, 2023-Kenya); sex workers in Mozambique reported hearing stories of violent crimes and murders occurring in client homes (Aantjes et al, 2023). Due to the criminalization of sex work, sex workers in Germany were reluctant to come forward if assaulted (Tümpel & Cardone, 2022). Participants in a study from the Dominican Republic also reported an increase in verbal, emotional and physical abuse from partners (Wang et al, 2022).…”
Section: Aggression and Violencementioning
confidence: 99%
“…Reasons for not being able to access financial support from the government included being non-status migrant workers (Benoit & Unsworth, 2022;Cubides Kovacsics et al, 2023;Fedorkó et al, 2022); not having paid taxes (Benoit & Unsworth, 2022;Callander et al, 2022;Cubides Kovacsics et al, 2023); living with relatives who had incomes (Gonzalez & Garrido, 2022); lacking the resources to apply for supports (Pearson et al, 2022); language barriers (Benoit & Unsworth, 2022;Cubides Kovacsics et al, 2023); having no bank account (Pearson et al, 2022); having no social insurance number (Benoit & Unsworth, 2022); not wanting to 'out' themselves as sex workers (Tümpel & Cardone, 2022); and having no documentable income (Benoit & Unsworth, 2022;Callander et al, 2022;Tan et al, 2021a). Many of these barriers were particularly relevant to migrant sex workers.…”
Section: Governmental Financial Supportmentioning
confidence: 99%